Leveraging high-performance HRM practices and knowledge sharing for managing technological and social change in emerging market healthcare providers - Malik, Ashish; Nguyen, Mai; Budhwar, Pawan; Chowdhury, Soumyadeb; Gugnani, Ritika (Technological forecasting & social change, 2024)
We investigate the factors that affect healthcare service innovation resulting from digitalization. We develop a conceptual model asserting that adopting digital technologies for healthcare service innovation will require effective knowledge-sharing antecedents and high-performance human resource management (HPHRM) practices. Using a grounded theory approach, we present evidence from the healthcare industry in an emerging market setting of multiple qualitative case studies. We note how HPHRM practices create a social context for employees and managers to share their knowledge through face-to-face and technologically-mediated applications for delivering innovative healthcare services. We highlight the importance of employee empowerment, job autonomy, social interaction ties, trust, and shared goals for improving knowledge sharing and developing innovative healthcare solutions. Therefore, our study highlights the impact on the design of workplaces engaged in developing innovative healthcare solutions and the role of specific HPHRM practices in supporting the same. •HPHRM practices are crucial for creating a social context that promotes knowledge-sharing among employees and managers.•Face-to-face interactions and technology applications are key for fostering innovative healthcare services.•Empowerment, job autonomy, and social ties are essential elements shaping the social context in healthcare workplaces.•Trust and shared goals are pivotal for enhancing knowledge sharing, facilitating the development of innovative healthcare solutions.•Our findings profoundly impact the design of workplaces focused on developing innovative healthcare solutions.